2021
DOI: 10.1038/s41375-021-01217-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 suppression enhances T-cell antitumor immunity and responses to checkpoint blockade in chronic lymphocytic leukemia

Abstract: T-cell dysfunction is a hallmark of B-cell Chronic Lymphocytic Leukemia (CLL). CLL cells downregulate T-cell responses by expressing regulatory molecules including programmed death ligand-1 (PD-L1) and Interleukin-10 (IL-10). Immune checkpoint blockade (ICB) aims to restore T-cell function by preventing the ligation of inhibitory receptors like PD-1, however most CLL patients do not respond well to this therapy. Thus, we investigated whether IL-10 suppression could enhance antitumor T-cell activity and improve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 59 publications
5
30
0
Order By: Relevance
“…Our in vitro cell killing result indicated that this humanized third-generation CAR-targeting IL-13Rα2 did not secrete increased IL-6 and expressed dramatic low levels of IL-10. Since IL-6 was identified to be a key driver of CRS, 24 while IL-10 was found to induce T cell dysfunction, 25 our results suggest a powerful anti-GBM potential in patients.…”
Section: Discussionmentioning
confidence: 61%
“…Our in vitro cell killing result indicated that this humanized third-generation CAR-targeting IL-13Rα2 did not secrete increased IL-6 and expressed dramatic low levels of IL-10. Since IL-6 was identified to be a key driver of CRS, 24 while IL-10 was found to induce T cell dysfunction, 25 our results suggest a powerful anti-GBM potential in patients.…”
Section: Discussionmentioning
confidence: 61%
“…The combination of anti-IL-10 with anti-PD-1 treatment in this model significantly inhibits tumor growth compared to treatment with either component alone [ 25 ]. Consistent with these observations, blocking IL-10 increases anti-tumor T cell activity and ICI responsiveness in a chronic lymphocytic leukemia mouse model [ 26 ]. Furthermore, in a phase II clinical trial, the serum levels of IL-10 prior to treatment have been shown to be associated with better efficacy in patients treated with nivolumab [ 27 , 28 ].…”
Section: Introductionsupporting
confidence: 53%
“…This is not in agreement with the fact that TNF favours the M1 macrophage phenotype, despite the current view of NLC being M2-polarized in the TME. On the other hand, IL-10 thwarts anti-tumoral immune responses, inhibits pro-inflammatory cytokines like TNF, and increases the level of pro-survival molecules such as ICAM-1 on the surface of CLL cells [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%